Characterization of the Collecting Electrode in ThermalBatteries by the X-ray Technique - N. ALKHATEEB, AHMED; H. HUSSEIN, FALAH; M. SARHAN, WALEED; D. OMRAN, KAREEM (Asian Journal of Chemistry, 2010)
In this study, a comparison of the X-ray diffraction values for the collecting electrode of the foreign thermal cell and the linear spectrum for this diffraction, respectively, has been carried out. Two peaks belonging Ni were recognized. Additionally, a further comparison has been performed for the X-ray diffraction values of the collecting electrode component of the assembled cell and the linear spectrum for this diffraction at different temperatures. The findings demonstrate that after running the cell at 400°C the electrode embraced the compounds, NiO and KCl, beside the elemental Ni. Furthermore, a similar comparison for the collecting electrode of the assembled thermal cell at 460°C has been perfonned. The outcome revealed the development of two peaks for Ni as well as one peak for the emerged NiO. This indicated the incomplete oxidation of Ni, even at the maximum temperature. Finally, another comparable study for the collecting electrode, belonging to the assembled thermal cell, has been brought about at 600°C. The developed peak demonstrated the formation of NiO as the final product.